(untitled) (LACCEI, 2024)
In the present degree work, the design of a SGG was carried out for the realization of degree projects (PG) in the Petrochemical Programs of the University of Cartagena. A SWOT analysis made it possible to identify the main weaknesses and threats that motivated the design of the proposed system, these being the existence of a single degree modality, low skills in students for the formulation of projects, absence of full-time teachers, content of the unsuitable subjects increase in the rate of permanence, increase in student desertion and exclusion from calls respectively. Subsequently, the design of the SGG was proposed for the efficient realization of PG, which had six elements: Governance system, indicators, templates, information system, procedure guide, and communication management. Finally, possible solutions to the deficiencies found were analyzed together with the project stakeholders and an action plan was proposed that allowed monitoring, improvement and evaluation of the indicators aligned with the strategies of the 2021-2031 research plan issued by the vice-rector’s office. of investigations of the University of Cartagena.